"The Diversity and Abundance of Echnodermata in the Waters of Tugulufa Beach, Tidore District, Tidore Kepulauan City" - Adha, Rizky Putri Fajrina; Ahmad, Muhammad Ali; Azis, Mahruf (Jurnal Ilmiah Wahana Pendidikan, 2026)
Echinodermata is one of the most important animals in the extratern ecosystem because it is useful as one of the components in food, organic waste eaters, and other small animals. This research aims to find out the diversity and abundance of Echinodermata in the Waters of Tugulufa Beach, Tidore District, Tidore Kepulauan City. The research was conducted using the quadratic transect method at four stations with observation of the type and number of individuals, as well as the measurement of environmental parameters. The results of the study found 11 species of Echinodermata, namely Holothuria atra (burned sea cucumber), Holothuria edulis (red sea cucumber), Holothuria scabra (sand sea cucumber), Protoreaster nodosus (sea star), Linckia laevigata (blue starfish), Archaster typicus (sand starfish), Diadema setosumm (Black pig hair), Echinothrix calamaris (sear zebra pig hair), Tripneustes gratilla (pig hair), and Ophiocoma scolopendrina (Snake starfish). The most dominant type is Protoreaster nodosus (Sea Starfish) (38 individuals) at stations I, II, and III, while Holothuria edulis (Red Starfish) (31 individuals) dominates at station IV. The species with the lowest number are H. scabra (Sandfish), A. typicus (Sand sea star), E. calamaris, and T. gratilla (Pig feathers) each of which only found one individual. Diversity values are classified as low to medium, with the largest number of types at station 4 (8 types). Environmental parameters show a temperature of 28–30°C, salinity of 30–32‰, and pH 6–7 which still supports the life of Echinodermata.